2016
DOI: 10.1002/uog.15876
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of 107 cases of fetal aortic stenosis from a European multicenter retrospective study

Abstract: Objectives Fetal aortic valvuloplasty (FV) aims to prevent fetal aortic valve stenosis progressing into hypoplastic left heart syndrome (HLHS), which results in postnatal univentricular (UV) circulation. Despite increasing numbers of FVs performed worldwide, the natural history of the disease in fetal life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 17 publications
6
70
3
1
Order By: Relevance
“…Natural history studies have demonstrated that in mid‐gestational fetuses with severe aortic stenosis and a normal‐sized or dilated left ventricle (LV), left heart growth arrest can occur leading to HLHS at birth . Echocardiographic‐derived hemodynamic parameters that are moderately predictive of development of HLHS in these fetuses include LV dysfunction, monophasic mitral valve (MV) inflow, retrograde systolic transverse aortic arch flow, and foramen ovale (FO) flow reversal …”
Section: Introductionmentioning
confidence: 99%
“…Natural history studies have demonstrated that in mid‐gestational fetuses with severe aortic stenosis and a normal‐sized or dilated left ventricle (LV), left heart growth arrest can occur leading to HLHS at birth . Echocardiographic‐derived hemodynamic parameters that are moderately predictive of development of HLHS in these fetuses include LV dysfunction, monophasic mitral valve (MV) inflow, retrograde systolic transverse aortic arch flow, and foramen ovale (FO) flow reversal …”
Section: Introductionmentioning
confidence: 99%
“…7 One method of assessing potential deviation from normality is by the use of z scores which describe the number of gestation-specific SDs a given measurement lies from the gestation-specific mean. 8 The impact of this method of assessment is well described in fetal cardiology particularly with respect to prediction of postnatal development of coarctation of the aorta, early neonatal intervention in tetralogy of Fallot and of single versus biventricular repair in cases of critical left or right ventricular outflow tract obstruction, 5,6,[9][10][11][12][13][14][15] and identification of suitable cases for fetal cardiac intervention. [16][17][18] Reference ranges of fetal outflow tracts have been published previously, but the number of cases examined was small ranging from 130 to 390.…”
mentioning
confidence: 99%
“…However, for some cardiac lesions, notably coarctation of the aorta, pulmonary valve stenosis, and aortic valve stenosis, the size of vessels is an important consideration both for diagnosis and prognosis. [3][4][5][6] It can be extremely important to compare an observed size of a valve or vessel to a size expected at a particular gestational age (GA). 7 One method of assessing potential deviation from normality is by the use of z scores which describe the number of gestation-specific SDs a given measurement lies from the gestation-specific mean.…”
mentioning
confidence: 99%
“…Given the lack of randomized trials in this field, it is still unclear whether the outcomes of intervention are better than the natural history of the disease and offset the increased risk of fetal death due to the procedure (6%–36%) . Indeed, Gardiner et al recently published a large “natural history” cohort that showed that approximately 1 in 3 fetuses fulfilling the criteria for intra‐uterine intervention still had a biventricular postnatal circulation, even without the procedure . As such, fetal aortic valvuloplasty remains experimental, and further refinement of selection criteria or a randomized controlled trial comparing intervention to expectant management with standardized postnatal care are urgently needed.…”
Section: Advances In Diagnosis and Treatment Of Fetal Cardiac Anomaliesmentioning
confidence: 99%
“…44,47,48 Indeed, Gardiner et al recently published a large "natural history" cohort that showed that approximately 1 in 3 fetuses fulfilling the criteria for intra-uterine intervention still had a biventricular postnatal circulation, even without the procedure. 49 As such, fetal aortic valvuloplasty remains experimental, and further refinement of selection criteria or a randomized controlled trial comparing intervention to expectant management with standardized postnatal care are urgently needed.…”
Section: Advances In Diagnosis and Treatment Of Fetal Cardiac Anomamentioning
confidence: 99%